Dampak Kebijakan Publik Terhadap Resiliensi dan Eskalasi UMKM di Kota Makassar: Studi Kebijakan Afirmatif, Transformasi Spasial, dan Digitalisasi Ekonomi (2020–2025) - Muhammad Nasir (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2025)
Abstract This study evaluates the strategic impact of the Makassar City Government's policies on the Micro, Small, and Medium Enterprises (MSME) ecosystem during the 2020–2025 period. Using a public policy analysis approach and regional economic empirical data, this study examines the effectiveness of the paradigm shift from supply-side interventions to demand-side interventions, as well as the integration of the Smart City concept in local economic empowerment. Key findings indicate that affirmative policies allocating 50% of the regional budget (APBD) and the Local E-Catalogue successfully created a significant captive market for formal MSMEs. The "Lorong Wisata" (Tourism Alley) program has proven effective in increasing micro-enterprise income at the grassroots level by up to 100% through a community-based tourism approach. In the digital sector, there was a surge in QRIS payment adoption by 171% year-on-year, although digital literacy gaps persist in operational management aspects. Nevertheless, structural challenges such as the complexity of OSS-RBA licensing and compliance with halal certification standards due to limited household production infrastructure remain barriers to formalization. This study recommends the establishment of shared production facilities and proactive legality assistance to ensure the inclusivity of the city's economic growth.